(untitled) (Altre Modernità, 2022)
In the vast literary production of A. P. Chekhov there are written testimonies of the cholera epidemic that struck Russia for the fifth time during 1892-1893. Approximately 400,000 deaths were recorded from this epidemic that began in India and Central Asia in 1883. As Chekhov’s profession was that of medical doctor, he dedicated himself to the farmers in the numerous villages situated in the area of his estate in Melichovo, refusing any monetary compensation. This experience is recorded both in the documents relative to his professional activity and in his letters. Critics consider these as an integral part of his literary production as they present the same stylistic and narrative characteristics. The present article will analyze the representation of these tragic events from a double perspective. On the one hand from the point of view of Chekhov-physician; on the other, as Chekhov-writer. The following aspects will be discussed: 1) the description of cholera as an animate being. This is a typical characteristic of mythologizing a disease in the collective imagination. 2) The description of the apocalyptic attitude in the population regarding the epidemic. It was given the status of divine punishment. 3) Consideration of the focal points of the epidemic as ʻdead spacesʼ.